From Truthiness to Drumpf: The Potentials and Limitations of Satirical News Shows as Critical Media Spectacles - Mna, Ilias Ben (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
The article discusses the cultural and political significance of popular satirical news shows in the US and their potential to form a counter-discourse to established news media from the perspective of younger viewers. Douglas Kellner's concept of the ccmedia spectacle" provides a primary theoreticalaccess to an analysis of the format and contents of such programs. In this context, the political economy, distribution avenues and the entertainment logic of, for example, The Colbert Report and The Daily Show are dissected and put into a larger socio political context. The confluence of a digital media environment and a language of pop culture-inflected irony is found to be a principalfoundation for the spectacle status of satirical news shows. A further discussion of Stephen Colbert's speech at the 2006 White House Correspondents Dinner illustrates the discursive power of these media spectacles in unmasking staged political performances and calling out the failures of established journalism. To a certain degree, satiricalnews shows can therefore be seen as filling a void, in that they act as a ufifth estateu that holds public power brokers accountable through a pop culture-friendly iconoclasm. Nevertheless, popular satirical news shows on major networks were also found to be largely structured by a neoliberal market logic and shaped by corporate ownership, which favors ..ideological corridors" wherein radical democratic politics or structural economic changes are repeatedly sidelined. In this sense, these programs perform within a stet of contradictions, in that they critique (conventional) media spectacles while perpetuating the logic of the spectacle.